Insights into the plant response to nematode invasion and modulation of host defense by plant parasitic nematode - Chen, Xiaolong; Li, Fuqiang; Wang, Ding; Cai, Liqun (Frontiers in Microbiology, 2024)
Plant pathogens cause diseases by suppressing plant immune response and interacting with plant cells. Investigating these interactions assists in decoding the molecular strategies the pathogen uses to overcome plant immunity. Among plant pathogens, the nematodes parasitizing various plants incur a profound impact on food production across the globe. To deal with these parasites, plants have developed a complicated defense system, including performed defenses like rigid cell walls and reinforcements acting as the first line of defense to combat any invader. Plants also have a wide diversity of constitutively released phytochemicals that are toxic to the invading microbes as their defense arsenals. Additionally, a substantial system of host responses is triggered in response to infection based on the abilities of the host plants to sense and recognize the invading pathogen. Nematodes have evolved the strategies to perceive and respond to host defense through their nervous system which help them escape, avoid, or neutralize the host plant defense systems. For developing an effective management strategy, it is crucial to understand the mechanism by which the nematode suppress the host defense. Previous reviews mainly discussed the interaction of plants with the nematodes for their immunity against nematodes. The present review will discuss the strategies employed by the plant parasitic nematodes for suppressing plant defense along with an overall insights into the basic nematode recognition mechanism and basal immunity response of the host plant. The mechanism of modulating host defense by nematodes including the role of their effectors were also discussed. The latest research progress about the release of metabolites by plants, and the mode of action of these defensive chemicals at the molecular level in combating the nematode invasion was also analyzed.